Developing sustainable business-to-business (B2B) strategies in service innovation for enhancing customer loyalty in the petrochemical industry: a systematic review - Oos Kosasih; Kadarisman Hidayat; Benny Hutahayan; Sunarti (Cogent Business & Management, 2024)
This research aims to provide a comprehensive understanding of the factors that drive successful sustainable service innovation and to offer practical guidelines for adopting these strategies in the petrochemical sector. The study employs a systematic literature review methodology, reviewing and synthesizing empirical data, theoretical frameworks, and case studies from peer-reviewed journals published between 1998 and 2024. A multi-database search strategy was utilized, incorporating keywords related to sustainability and service innovation. The selection process followed a PRISMA flow diagram to ensure the inclusion of relevant and high-quality sources. The results highlight several key factors driving sustainable service innovation, including stakeholder engagement, sustainability policies, growth frameworks, and specific determinants of service innovation such as organizational culture, leadership, and technology. This study provides valuable insights for managers and policymakers on promoting and implementing sustainable service innovation to achieve long-term sustainability goals. The comprehensive analysis presented in this research offers a roadmap for petrochemical companies to navigate the complexities of sustainability while maintaining customer loyalty and ensuring economic viability in a rapidly evolving market. This study contributes to the existing body of knowledge by detailing the determinants of sustainable service innovation and their practical application in the petrochemical industry.
Keywords: 650; Customer loyalty; sustainable service innovation; petrochemical industry; sustainability policies; PRISMA